2020
DOI: 10.35530/it.071.03.1826
|View full text |Cite
|
Sign up to set email alerts
|

The effects of online marketing on financial performance in the textile industry

Abstract: Although Romania has an Internet penetration rate of 73.8%, over the world average, below the European Union average of 85.2%, Romanian Internet users ranked 28th in online shopping, the lowest position in EU, while the Romanian enterprises are the least digital in the EU ranking on the lowest positions in using social media and e-commerce. The aim of this paper is to examine the impact of using online marketing tools in the development and implementation of marketing strategies and their impact on org… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 0 publications
1
14
0
Order By: Relevance
“…Since the Internet's inception, the process of transitioning from a text-based communications economy to a much more complicated data stream based on picture, video material, and metadata linked to location, date, and mood has grown into a considerably more complex data stream (Orzan et al, 2020). The growth of WIFI and 5G enabled a new generation of the unlocated social, and human-machine internationalization became a bidirectional hybrid telemetry, resulting in the connection between computerized health networks that allow medical data synergy (radiographs, CT scans and MRI).…”
Section: Methodology -Big Data and Machine Learningmentioning
confidence: 99%
“…Since the Internet's inception, the process of transitioning from a text-based communications economy to a much more complicated data stream based on picture, video material, and metadata linked to location, date, and mood has grown into a considerably more complex data stream (Orzan et al, 2020). The growth of WIFI and 5G enabled a new generation of the unlocated social, and human-machine internationalization became a bidirectional hybrid telemetry, resulting in the connection between computerized health networks that allow medical data synergy (radiographs, CT scans and MRI).…”
Section: Methodology -Big Data and Machine Learningmentioning
confidence: 99%
“…Temperature dynamics is a significant branch of physics. With the advent of the steam engine and the subsequent actions taken in order to enhance it, the development of what we now know as thermodynamics occurred (Orzan et al, 2020). The three laws of thermodynamics were discussed in depth during physics classes.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The impact of using online marketing tools on a company's performance was examined by Orzan et al [20], based on a questionnaire addressed to Romanian companies in the textile industry (production, distribution, or retail) and found that online marketing had a positive impact on organizational performance.…”
Section: Literature Reviewmentioning
confidence: 99%